Seronegative Rubella IgG Status in Pregnant Women Visiting Tertiary Care Hospital - Atifa Afsheen Sharique; Muhammad Sharique; Asha Mahesh; Syed Wajahat Shah (Journal of Bahria University Medical and Dental College)
Objective: To determine the seronegative rubella IgG status in pregnant women visiting antenatal clinic at Jinnah Medical College Hospital.